A deadly tail - Lyle, Dixie (Lyle, Dixie. Whiskey, Tango & Foxtrot mystery., 2016)
Foxtrot has seen a lot of strange things as assistant to billionaire Zelda Zoransky at her wacky mansion. And that includes her telepathic cat Tango and ectoplasmic pooch Whiskey. So it's no surprise to find a horde of zombies lurching across the lawn-even if they are just actors in a horror movie that's filming on the mansion grounds. The special effects look pretty convincing. But all that fake blood doesn't fool Whiskey, who quickly sniffs out the truth: one of those corpses is real...